A proof of concept treatment planning study of gated proton radiotherapy for cardiac soft tissue sarcoma. (July 2021) - Lee, Hyeri; Pursley, Jennifer; Lu, Hsiao-Ming; Adams, Judith; DeLaney, Thomas; Chen, Yen-Lin; Jee, Kyung-Wook
Highlights: Challenges of a cardiac target due to the respiration, the heart motion and the interplay effect. Cardiac respiratory double gating with additional ECG signals for proton radiotherapy. Proton planning study with a cardiac-gated CT scan obtained at the end-expiration. Abstract: Background and Purpose: Few studies on radiotherapy of cardiac targets exist, and none using a gating method according to cardiac movement. This study aimed to evaluate the dose-volume advantage of using cardiac-respiratory double gating (CRDG) in terms of target location with additional ECG signals in comparison to respiratory single gating (RSG) for proton radiotherapy of targets in the heart. Materials and Methods: Cardiac motion was modeled using a cardiac-gated four-dimensional computed tomography scan obtained at the end-expiration. Plans with the prescription dose of 50 Gy (RSG and CRDG plans at diastole and systole phases) were compared in terms of clinically relevant dose-volume criteria for various target sizes and seven cardiac subsites. Potential dose sparing by utilizing CRDG over RSG was quantified in terms of surrounding organ at risk (OAR) doses while the dose coverage to the targets was fully ensured. Results: The average mean dose reductions were 28 ± 10% when gated at diastole and 21 ± 12% at systole in heart and 30 ± 17% at diastole and 8 ± 9% at systole in left ventricle compared to respiratory single gating. The diastole phase was optimal for gated treatments for all target locations except right ventricle and interventricular septum. The right ventricle target was best treated at the systole phase. However, an optimal gating phase for the interventricular septum target could not be determined. Conclusions: We have studied the dose-volume benefits of CRDG for each cardiac subsite, and demonstrated that CRDG may spare organs at risk better than RSG.